Can Be Beauty Calculated? - Demuth, Andrej; Demuthova, Slavka (European Scientific Journal, ESJ, 2017)
In this study we focus on three historical concepts of using of mathematical approach to beauty and aesthetic (taste) standard of mathematical thinking in early formation of modern aesthetics of the eighteenth century. The first is Hume’s idea of statistical standardization and the significance of rareness and excellence, as a desire for specific positive deviation. Second model of aesthetic thinking is Reid’s aesthetic realism. In this theory of taste and art the attention is paid to the study of the parameters and attributes of objects, as well as to the fact that a beautiful object contains cognitively significant information. Those who perceive it are, or should be, able to deal with and understand this information. Important part of these considerations is the analysis of ontological status of beauty and the term of excellence. In the conclusion of this study, we try to highlight the mathematical algorithm of aesthetic standards creation and ideal in Kant’s Critique of Judgment. We attempt to suggest the potential of all three approaches in contemporary scientific cognitive aesthetic research.